DDX58(RIG-I)-related disease is associated with tissue-specific interferon pathway activation. Issue 3 (25th January 2021) - Prasov, Lev; Bohnsack, Brenda L; El Husny, Antonette S; Tsoi, Lam C; Guan, Bin; Kahlenberg, J Michelle; Almeida, Edmundo; Wang, Haitao; Cowen, Edward W; De Jesus, Adriana A; Jani, Priyam; Billi, Allison C; et al.
Abstract : Background: Singleton-Merten syndrome (SGMRT) is a rare immunogenetic disorder that variably features juvenile open-angle glaucoma (JOAG), psoriasiform skin rash, aortic calcifications and skeletal and dental dysplasia. Few families have been described and the genotypic and phenotypic spectrum is poorly defined, with variants in DDX58 (DExD/H-box helicase 58) being one of two identified causes, classified as SGMRT2. Methods: Families underwent deep systemic phenotyping and exome sequencing. Functional characterisation with in vitro luciferase assays and in vivo interferon signature using bulk and single cell RNA sequencing was performed. Results: We have identified a novel DDX58 variant c.1529A>T p.(Glu510Val) that segregates with disease in two families with SGMRT2. Patients in these families have widely variable phenotypic features and different ethnic background, with some being severely affected by systemic features and others solely with glaucoma. JOAG was present in all individuals affected with the syndrome. Furthermore, detailed evaluation of skin rash in one patient revealed sparse inflammatory infiltrates in a unique distribution. Functional analysis showed that the DDX58 variant is a dominant gain-of-function activator of interferon pathways in the absence of exogenous RNA ligands. Single cell RNA sequencing of patient lesional skin revealed a cellular activation of interferon-stimulated gene expression in keratinocytes and fibroblasts but not in neighbouring healthy skin. Conclusions: These results expand the genotypic spectrum of DDX58-associated disease, provide the first detailed description of ocular and dermatological phenotypes, expand our understanding of the molecular pathogenesis of this condition and provide a platform for testing response to therapy.